Mechanism of Photoinitiated Free Radical Polymerization by Thioxanthone-Anthracene in the Presence of Air - Balta, Demet Karaca; Arsu, Nergis; Yagci, Yusuf; Sundaresan, Arun K.; Jockusch, Steffen; Turro, Nicholas J. (AMER CHEMICAL SOC, 2011)
The mechanism of formation of initiating radicals for free radical polymerization by the thioxanthone anthracene (TX-A) photoinitiator was investigated by laser flash photolysis, fluorescence and phosphorescence spectroscopy, and polymerization studies. The proposed mechanism of photoinitiation involves photoexcitation of TX-A and quenching of triplet excited states of TX-A by molecular oxygen to generate singlet oxygen. Singlet oxygen reacts with the anthracene moiety of TX-A to form an endoperoxide. The endoperoxide intermediate was isolated and characterized by MS and H-1 NMR The endoperoxide undergoes photochemical or thermal decomposition to generate radicals which are able to initiate free radical polymerization. A significant deuterium effect on the polymerization rates using CDCl3 and CHCl3 as solvents confirmed the involvement of singlet oxygen in the initiation process.
Keywords: CHAIN THIOXANTHONE; SINGLET OXYGEN; Polymer Science